Estimation of center of mass velocity by right posterior spine iliac landmark during countermovement jump - Brady, C. J.; Harrison, A. J.; Flanagan, F. P.; Comyns, T. M. (ISBS Proceedings Archive (Michigan), 2017)
When the impulse phase is proceeded by approach movement (e.g. volleyball spike jump), the vertical velocity of CoM at the beginning of the impulse phase must be known. To reduce the number of landmarks, the aim of this study was to verify the concordance between the velocity of CoM and the Right Posterior Spine Iliac at touchdown after flight phase. Ten female volleyball players of the first national volleyball league of Austria performed ten maximal CMJ without arm movement. Paired t-test was used to compare velocities between the two methods. No significant differences between the methods with maximal individual differences lower than 0.1m/s at touchdown could be found. If only the landing velocity at touchdown must be known, it seems to be sufficient to determine the velocity of Right Posterior Spine Iliac landmark.